Pengaruh strategi konflik kognitif terhadap tingkat pemahaman siswa kelas X materi energi dan momentum di SMAN 5 Bukittinggi - Risa Rafika Sari; Amali Putra; Asrizal Asrizal (PILLAR OF PHYSICS EDUCATION, 2019)
One of Unesco pillars, learning to know or learning to learn, should become the underlying principles in learning process. Students are expected to understand the concepts that they have had learned comprehensively and applied them in real world problems. But reality shows that student comprehension level is so low and there is a lot of misconceptions that exist. This study aims to elicit the effect of conflict cognitive strategy upon the comprehension level of tenth grader students in SMAN 5 Bukittinggi. This study is conducted by using pre-experimental method with one group pretest-posttest design. Data of research are collected through answer sheet equipped with modified Certainty of Response Index (CRI) technique in which students choose their answers and certainty indexes accompanied with reasons of their answers. Hypothesis testing uses Wilcoxon test with signifincane level 0.05. Since the calculated value (Zcount) is beyond the acceptance area of critical value (Ztable), it means that the null hypothesis (H0) is rejected. This result brings conclusion that there is statistically difference of students’ comprehension level before the implementation of conflict cognitive strategy compared to one after the strategy has been being applied. Application of cognitive conflict strategy yields effect on students’ conceptual understanding, wherein it increase percentage of students that understand concepts and decrease percentage of students who bear misconception and those who do not know concepts.